Barley growing in cerrado soils in the dry season under irrigation - Silva, Ady Raul da; Andrade, José Maria Vilela de (Pesquisa Agropecuaria Brasileira, 2014)
The Results of the National. Barley Yield Trial grown at the headquarters of the Centro de Pesquisa Agropecuária dos Cerrados of EMBRAPA in the Federal District has shown good conditions for barley production in the dry season under irrigation. The yields were high in the five years, and the lowest yield in one year, was still satisfactory. The grain quality was measured by its germinative power and energy. Its size and health conditions were excellent in all five years. The main limitation for the crop was the high protein content, observed during some years, a factor that has to be solved before the region is recommended for malting barley production. A comparison with the barley cultivation in the temperate climatic region in the South of Brazil shows that the Federal District region offers better conditions in all respects except for protein content. It is recommended that the research with barley be intensified in parallel with wheat because of the similiarities of requirements of the two crops and the results point out the possibility of the region to play an important role to the national self-sufficiency goal.